Faktor-Faktor Yang Berhubungan Dengan Vaksinasi Covid-19 Dikomplek Villa Pertiwi Depok Jawa Barat - Rania Irwan; Milla Evelianti Saputri; Tommy J. F. Wowor (Malahayati Nursing Journal, 2022)
ABSTRACTCoronavirus disease 2019 (Covid 19) is an infectious disease that is becoming a global pandemic. In 2020, millions of people will fall ill and die from this disease every day. One of the ways to prevent exposure to COVID-19 is through the Covid-19 vaccination. The Covid-19 vaccine is one of the government's breakthroughs to fight and deal with Covid-19 in the world, especially the State of Indonesia. The purpose of the Covid-19 vaccination is to reduce the spread of Covid-19, reduce morbidity and mortality caused by Covid-19, achieve immunity and protect the community from Covid-19, so as to protect society and the economy. To find out the relationship between age, gender, education, knowledge, and attitudes regarding Covid-19 vaccination. This study uses a quantitative method with a Cross Sectional approach. Sampling using random sampling technique. The measurement method is using a questionnaire with a measuring instrument using a questionnaire and the data obtained will be analyzed univariately and bivariately using the Chi Square test. The results of this study show that the p value is 0.014 0.05, meaning that there is a relationship between age and Covid-19 vaccination at the Villa Pertiwi Depok Complex in 2021, the p value is 0.000 0.05, meaning that there is a sex relationship with Covid vaccination-19 at the Villa Pertiwi Depok Complex in 2021, the p value is 0.014 0.05, meaning that there is a relationship between education and Covid-19 vaccination at the Villa Pertiwi Depok Complex in 2021, the p value is 0.008 0.05, meaning there is a relationship knowledge with the Covid-19 vaccination at the Villa Pertiwi Depok Complex in 2021, the p value of 0.000 0.05, it means that there is a relationship between attitude and the Covid-19 vaccination at the Villa Pertiwi Depok Complex in 2021. There is a relationship between knowledge and attitudes regarding COVID-19 vaccination at the age of 12-59 years with female and male sex with elementary to university education Keywords : Covid-19, Knowledge, Attitude, Vaccinations ABSTRAK Penyakit Coronavirus 2019 (Covid 19) merupakan penyakit infeksi yang sedang menjadi pandemi global. Pada tahun 2020, jutaan orang akan jatuh sakit dan meninggal akibat penyakit ini setiap hari.Salah satu pencegahan terpapar nya covid-19 melalui vaksinasi Covid-19. Vaksin Covid-19 merupakan salah satu terobosan pemerintah untuk melawan dan menangani Covid-19 yang ada didunia khususnya Negara Indonesia. Tujuan dari vaksinasi Covid-19 adalah untuk mengurangi penyebaran Covid-19, menurunkan angka kesakitan dan kematian yang disebabkan oleh Covid-19, mencapai kekebalan dan melindungi masyarakat dari Covid-19, sehingga dapat menjaga masyarakat dan perekonomian. Untuk mengetahui adanya hubungan antara Usia, jenis kelamin, pendidikan, pengetahuan, dan sikap mengenai vaksinasi Covid-19. Penelitian ini menggunakan metoden kuantitatif dengan pendekatan Cross Sectional. Pengambilan sampel menggunakan  teknik random sampling . Cara ukur menggunakan angket dengan alat ukur menggunakan kuisioner dan data yang diperoleh akan dianalisis secara univariat dan bivariat menggunakan uji Chi Square. Hasil penelitian ini menjukkan bahwa  nilai p value sebesar 0,014 ≤ 0,05, berarti adanya hubungan usia dengan vaksinasi Covid-19 di Komplek Villa Pertiwi Depok tahun 2021, nilai p value sebesar 0,000 ≤ 0,05, berarti adanya hubungan jenis kelamin dengan vaksinasi Covid-19 di Komplek Villa Pertiwi Depok tahun 2021, nilai p value sebesar 0,014 ≤ 0,05, berarti adanya hubungan pendidikan dengan vaksinasi Covid-19 di Komplek Villa Pertiwi Depok tahun 2021, nilai p value sebesar 0,008 ≤ 0,05, berarti adanya hubungan pengetahuan dengan vaksinasi Covid-19 di Komplek Villa Pertiwi Depok tahun 2021, nilai p value sebesar 0,000 ≤ 0,05, berarti adanya hubungan sikap dengan vaksinasi Covid-19 di Komplek Villa Pertiwi Depok tahun 2021. Terdapat hubungan antara pengetahuan dan sikap mengenai vanksinasi covid-19 pada umur 12-59 tahun dengan jenis kelamin perempuan dan laki-laki dengan pendidikan SD sampai Perguruan tinggi. Kata Kunci : Covid-19, Pengetahuan, Sikap, Vaksinasi